Methods of examination of agglutinant sands and quality of decorative and jewelry castings - L. A. Ivanova; S. L. Zelenkov; N. L. Zamjatin (Литьë и металлургия)
Perspectives of use of plaster agglutinant sands for improvement of quality of decorative and jewelry casting